Farming of Indigenous Crayfish in Russia: A Mini-Review of Recent Studies - Alexander G. Dvoretsky; Vladimir G. Dvoretsky (Animals)
Natural populations of crayfish in Europe have experienced significant declines due to the spread of crayfish plague, overfishing, competition with invasive crayfish species, and habitat degradation. Consequently, crayfish farming has gained importance in meeting the increasing demand for crayfish products. Although Russia boasts abundant water resources, the development of crayfish aquaculture remains nascent. In this review, we consolidate recent studies by Russian researchers that focus on various aspects of crayfish cultivation. Extensive cultivation in open ponds is the most suitable method, owing to its accessibility and lower costs; however, it necessitates suitable environmental conditions within the water bodies. The production cycle encompasses pond preparation, stocking, exploration, restoration, and monitoring. Controlled cultivation of egg-bearing females is essential for producing high-quality seedstock for subsequent rearing. Experimental evidence suggests that crayfish exhibit high adaptability to artificial conditions, with formulated diets comprising artificial feeds for sturgeon and powdered dried beef by-products demonstrating promising results in terms of growth performance. Plastic tangled threads and mink shelters are recommended to reduce cannibalism. Short-term grow-out of juvenile crayfish can yield a profit margin of 17%, while a complete two-year production cycle is projected to achieve financial break-even over three years. The primary challenges confronting the industry include disease management, cannibalism, the need for skilled technical personnel, and insufficient financial and policy support.